Navigating Barriers to Self-Declared Halal Certification among Culinary MSMEs in Banten - Moh. Nasrudin; Rahmatullah, Rahmatullah (Jurnal Halal Center, 2026)
This research explores the lived experiences of culinary MSMEs in Banten, Indonesia, as they navigate the complexities of the mandatory Self-Declare Halal certification scheme. Employing a qualitative phenomenological approach, the research investigates how traditional entrepreneurs perceive and overcome systemic technical and psychological barriers. Findings reveal that while digital literacy gaps and “regulatory anxiety” regarding potential hidden costs initially hinder compliance, entrepreneurs successfully mitigate these obstacles through a multi-layered orchestration of support. This process involves symbiotic collaborations with Halal Product Process Assistants (P3H), strategic use of local social capital, and implementation of micro-innovations in operational management. Upon obtaining certification, a profound semantic shift occurs as the Halal label shifts from a purely spiritual obligation to a strategic market asset, fostering an enhanced entrepreneurial identity and long-term sustainability. The research concludes that optimizing the Halal ecosystem requires transitioning from a rigid top-down regulatory model to a more empathetic, humanized, and localized support system that recognizes the socio-cultural realities of the culinary grassroots.
Keywords: Array